Conceptual obstacles to making use of four smoking-cessation strategies: What reasons do light smokers give for rejecting strategies?. Issue 2 (22nd December 2015) - Ryan, Michael P; Hinojosa, Jennifer J
Some smokers have safety and cost concerns about nicotine replacement therapy which discourage its use. We recruited 56 young adult light smokers to read detailed descriptions of a hybrid nicotine replacement therapy, a prescription drug treatment, scheduled reduced smoking, and a menu of self-help tactics. Participants listed five reasons smokers might reject each strategy. An emergent-category content analysis classified each response with a high degree of inter-rater reliability. Only one-third of 32 concerns were strategy-specific; the majority focused on the general difficulty of quitting. Most prevalent were "continued cravings, " "addiction too strong, " "takes too long, " and "won't work." These and other concerns reflect conceptual obstacles to be surmounted in smoking-cessation interventions.